2009
DOI: 10.1093/pcp/pcp133
|View full text |Cite
|
Sign up to set email alerts
|

Rice BRITTLE CULM 5 (BRITTLE NODE) is Involved in Secondary Cell Wall Formation in the Sclerenchyma Tissue of Nodes

Abstract: Several brittle culm (bc) mutants known in grasses are considered excellent materials to study the process of secondary cell wall formation. The brittle phenotype of the rice bc5 (brittle node) mutant appears exclusively in the developed nodes, which is distinct from other bc mutants (bc1, 2, 3, 4, 6 and 7) that show the brittle phenotype in culms and leaves. To address the defects of the rice bc5 mutant in node-specific cell wall formation, we analyzed tissue morphology and cell wall composition. The bc5 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…A thorough understanding of any regulating mechanism, including the identification of transcription factors Aohara et al, 2009) would also certainly increase our understanding of xylan biosynthesis in the context of primary and secondary cell wall elaboration and would offer op-…”
Section: Resultsmentioning
confidence: 99%
“…A thorough understanding of any regulating mechanism, including the identification of transcription factors Aohara et al, 2009) would also certainly increase our understanding of xylan biosynthesis in the context of primary and secondary cell wall elaboration and would offer op-…”
Section: Resultsmentioning
confidence: 99%
“…CTAB is a cationic surfactant providing a buffer solution for dissociation and selective precipitation of DNA from histone proteins (Allen et al, 2006). Monocot plant cell walls have a unique structure (Aohara et al, 2009). Lignification of cereal cell walls makes degradation difficult, which results in restricted DNA extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Although bc10 shows reduced cellulose content, the localization BC10 proteins to the Golgi apparatus suggests that BC10 is not directly involved in cellulose synthesis, which takes place at the plasma membrane. Most recently, Aohara et al (2009) characterized the rice bc5 mutant, which speciWcally causes brittleness of the developed nodes without aVecting other plant parts. Although BC5 gene remains to be isolated, mapping of BC5 demonstrated that any known cell wall related genes do not exist in the BC5 locus.…”
Section: Introductionmentioning
confidence: 99%